Pregnancy-related Deaths in Rural Rajasthan, India: Exploring Causes, Context, and Care-seeking Through Verbal Autopsy - Iyengar, Kirti; Iyengar, Sharad D; Suhalka, Virendra; Dashora, Kalpana (Journal of Health, Population and Nutrition, 2009)
In 2002-2003, all deaths (n=156) of women aged 15-49 years in a block of southern Rajasthan were investigated to determine the cause of death and care-seeking behaviour. Family members of 156 (98%) of 160 deceased women were interviewed following the comprehensive listing of all deaths among women of reproductive age. Of the 156 deaths, 31 (20%) were pregnancy-related; 77% of these women died during the postpartum period, and 74% of the deaths occurred in the home. Direct and indirect obstetric causes were responsible for 58% and 29% of the deaths respectively; 12% were injury-related deaths. Medical care was sought for 65% of the women, and 29% were hospitalized. Family perception of not being able to afford treatment at distant hospitals was a major barrier to seeking care, and 60% of those who sought care had to borrow money for treatment. Lack of skilled attendance and immediate postpartum care were major factors contributing to deaths. Improved access to emergency obstetric care facilities in rural areas and steps to eliminate costs at public hospitals would be crucial to prevent pregnancy-related deaths. Key words: Behaviour; Care-seeking; Maternal mortality; Pregnancy; Pregnancy complications; Rural health; Verbal autopsy; India doi: 10.3329/jhpn.v27i2.3370 J Health Popul Nutr 2009 April;27(2):293-302